ENGLISH SPEECH SOUNDS [θ ð], [ʃ ʒ], [ʧ ʤ]: HOW ARE THEY REALIZED? - Katharina Rustipa (Dinamika Bahasa dan Budaya, 2009)
Languages vary considerably in the types of consonants which occur. Certain types of consonants are easier to produce than the others. Most students have difficulty in pronouncing [θ ð], [ʃ ʒ], [ʧ ʤ] since these sounds are not found in neither Indonesian nor Javanese. They tend to realize these sounds in other sounds. This article reports the realization of [θ ð], [ʃ ʒ], [ʧ ʤ] by the Indonesian students learning English. The data were obtained by means of recording 20 students reading words, phrases, and sentences containing [θ ð], [ʃ ʒ], [ʧ ʤ]. The unit of analysis of the study is words containing [θ ð], [ʃ ʒ], [ʧ ʤ]. Every word containing [θ ð], [ʃ ʒ], [ʧ ʤ] is transcribed. The correct pronunciation (for every research subject) for each pair of [θ ð], [ʃ ʒ], [ʧ ʤ] are counted to find out which one is more difficult for the student. The incorrect pronunciations for each pair of [θ ð], [ʃ ʒ], [ʧ ʤ] are analyzed in terms of the strategies (with what speech sound the student replaces). The research results show that [θ ʃ ʧ] are easier for the students to pronounce than [ð ʒ ʤ]. This is as what said by Hecht and Mulford (1982) that learners acquire voiceless consonants before the voiced consonants. The students employ transfer strategies when they find difficulties in pronouncing [θ ð], [ʃ ʒ], [ʧ ʤ]. They replace [θ] with [t], [s]; [ð] with [d], [θ], [nd]; [ʃ] with [s]; [ʒ] with [z], [ʃ]; [ʧ] with [c]; [ʤ] with [j]. Based on the findings, some suggestions can be put forward as follows: 1) The students should be taught the manner and point of articulation of [θ ð], [ʃ ʒ], [ʧ ʤ] so that they can produce those sounds correctly, 2) The students should be reminded that mispronunciation may cause misunderstanding. Key words: realization, transfer strategy, place of articulation, manner of articulation, adoption strategy, interlanguage